COMPARATIVE ANALYSIS OF ENGLISH TRANSLATIONS OF SURAH AL-'ALAQ: A CASE STUDY OF MY.SURAH AND THE QURAN TRANSLATION PLATFORM - Nadia, Aghnia Assifa; Liswati, Helli Ramdanniah; Syahid, Abdul Syahid (Faculty of Languages and Literature, Universitas Negeri Makassar, 2025)
This study presents a comparative analysis of English translations of Surah Al-'Alaq featured on two prominent digital platforms: My.Surah and Alquran-Terjemahan. With the increasing reliance on online Quranic resources, translations serve as a crucial link between the Arabic text and a global audience. Employing a qualitative descriptive approach, the research utilizes comparative textual analysis, emphasizing lexical choices, syntactic patterns, and theological nuances. Data were gathered from English translations of verses 1-19 on both platforms, and findings reveal notable differences: My.Surah employs a dynamic equivalence approach with simplified and communicative language, whereas Alquran-Terjemahan adopts formal equivalence, maintaining structural and lexical precision. These disparities impact reader perception, particularly concerning divine commands and theological interpretations. This research contributes to the field of Quran translation by illustrating how digital platform strategies influence meaning transmission. Further research is recommended to broaden the sample, incorporate reader perspectives, and explore the cultural reception of digital Quran translations.